Pengaruh Kualitas Produk dan Religiusitas Terhadap Keputusan Nasabah dalam Memilih Asuransi Syariah di PT. Prudential Life Anssurance Cabang Kota Gorontalo - Sofhian Sofhian; Sri Nur Ain Suleman (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2017)
This study aims to determine the Effect of Product Quality and Religiosity on customer decisionsin choosing Islamic insurance at PT.Prudential Life Anssurance Branch of Gorontalo City, with asample size of 177 respondents using random sampling method. This study uses multiple regressionanalysis tool on primary data found that the factor of Product Quality have positive andsignificant influence to customer decision to choose sharia insurance and religiosity have positiveand significant influence to customer decision to choose sharia insurance.The result of hypothesis test simultaneously (Test F) from both independent variables withFhitung equal to 80,111 in area of Ho rejected. This means that simultaneously factor of productquality and religiosity have a positive and significant influence to the decision of customers tochoose sharia insurance in PT. Prudential Life Ansurance Branch of Gorontalo City.Determination coefficient value of both independent variables obtained results of 0.479, it meansthat the Effect of Product Quality and Religiosity on customer decisions in choosing shariainsurance in PT.Prudential Life Anssurance Branch of Gorontalo City of 47.9% and the rest of52.1% influenced by other variables Which were not included in this study. Other variables may bepresent in marketing mix such as: promotion, people, place, process, and physical evidence.